Phylogenetic Scenario of Port-City Chickens in China Based on Two-Marker Types - Olowofeso, O.; Wang, J.Y.; Xie, K.Z.; Liu, G.Q. (International Journal of Poultry Science, 2005)
To detect the genetic lineage of four ubiquitous port-city (Haimen) chicken populations in China, a genetic study involving two-marker types viz: random and microsatellite markers were used with the genomic DNAs isolated from the chicken populations. A total of two hundred and forty genomic DNAs with 60 samples from each of Rugao, Jiangchun, Wan-Nan and Cshiqishi populations were used. All samples were subjected to both 45 and 35 cycles of amplifications with five random and fifteen microsatellite markers in polymerase chain reactions (PCRs), respectively. Average band-sharing coefficient (BSC) and the Nei standard genetic distances (Dij) obtained using the data generated by the random markers with the genomic DNAs. Using the microsatellite markers with the same set of genomic DNAs, allele frequencies were obtained through direct gene counting approach. The generated allele frequencies were used to compute the (Dij) between populations. With the random markers, the (Dij) obtained ranged from 0.0083 (Jiangchun and Cshiqishi) to 0.2789 (Rugao and Wan-Nan); while that of microsatellite markers ranged from 0.2360 (Rugao and Jiangchun) to 0.5072 (Rugao and Cshiqishi), respectively. Phylogenetic trees developed using both standard (Dij`s) revealed significant variations in the level of divergence between populations. Phylogenetic linkage of these chicken populations based on the random markers showed Jiangchun and Cshiqishi to be well related, whereas Rugao and Wan-Nan distantly related. For the microsatellite markers, Rugao and Jiangchun appeared very close, while Rugao and Cshiqishi populations appeared remote between the populations. The results emanated from the application of these markers with these chicken populations suggests that Jiangchun and Cshiqishi and or Rugao and Jiangchun are likely to have originated from the same source and Wan-Nan intermediate in both cases of the phylogeny trees, might had been developed through crossbreeding activities of these populations.